2016
DOI: 10.1111/fwb.12780
|View full text |Cite
|
Sign up to set email alerts
|

Carbon emission along a eutrophication gradient in temperate riverine wetlands: effect of primary productivity and plant community composition

Abstract: International audience1. Eutrophication increases primary productivity and favours the predominance of floating vegetation in wetlands. Carbon (C) fluxes in wetlands are strongly driven by primary productivity and can differ by vegetation type. However, to the best of our knowledge, the role of eutrophication in C fluxes has rarely been assessed. 2. Consequently, we aimed to measure the seasonal variation in carbon dioxide (CO2) and methane (CH4) fluxes at six aquatic sites in four temperate wetlands, ranging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 88 publications
0
23
0
1
Order By: Relevance
“…() suggested such a method as a tool for assessing diffusion and ebullition, while Grasset et al. () was one of the first studies to include ebullition data from these newer gas analysers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…() suggested such a method as a tool for assessing diffusion and ebullition, while Grasset et al. () was one of the first studies to include ebullition data from these newer gas analysers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when no linear regression trend was observed to determine the flux, we used the initial and end points to determine the sum of diffusive and ebullitive CH 4 fluxes, as discussed by Goodrich, Varner, Frolking, Duncan, and Crill (2011), Zhao et al (2015) and Grasset, Abril, Guillard, Delolme, and Bornette (2016). We acknowledge that our sampling procedure may not accurately measure diel gas emissions, as previous studies have found large variations in diel CH 4 and CO 2 fluxes (Liu et al, 2016;Natchimuthu, Selvam, & Bastviken, 2014;Natchimuthu et al, 2016).…”
Section: Greenhouse Gas Flux Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…; Grasset et al. ). Among the changes that affect wetlands, increasing use of water resources, together with climate change, is leading to periodic or chronic water deficits and, consequently, to large seasonal variations in water levels (Arnell ; Lehner et al.…”
Section: Introductionmentioning
confidence: 97%
“…Invasive macrophytes are typically faster growing and produce more biomass than native species (Herb & Stefan, 2006;Kennedy, Horth, & Carr, 2009). Macrophyte productivity impacts carbon (C) budgets of freshwater lakes directly via photosynthesis and autotrophic respiration and indirectly due to the degradation of plant litter (Carmichael, Bernhardt, Brauer, & Smith, 2014;Grasset, Abril, Guillard, Delolme, & Bornette, 2016). Therefore, significant changes in life forms of primary producers, such as those resulting from plant invasions, have the potential to change the net C flux of a lake (Attermeyer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%